Company Characteristics, Profitability and Sustainability Reporting in Companies Registered on BEI 2018-2020 - I Gusti Ayu Shinta Suryani; I Gusti Ngurah Agung Suaryana (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
Sustainability reporting is a voluntary report containing information on the social and environmental activities of the company that provides information on the company's environmental and social responsibility which is prepared based on the Sustainability Report Global Reporting Initiative (GRI) Guidelines. This research was conducted on 45 companies that won The Asia Sustainability Reporting Rating Award (ASRRAT) during the 2018-2020 period with the saturated sampling method. Data was collected by observing documentation and then analyzed by multiple linear regression. The results of this study indicate that firm size, profitability, firm age, and the size of the board of commissioners have no effect on sustainable reporting. This study shows that not all company characteristics proposed in previous studies have an effect on the disclosure of sustainability reporting.